EXPLORING PURA AGUNG GIRI NATHA AS THE BALI OF CENTRAL JAVA - Puji Lestari Nata; Nina Mistriani (UHN I Gusti Bagus Sugriwa Denpasar, 2025)
This study aims to explore and analyze the tourist attractions of Pura Agung Giri Natha which is known as the